Socio-cultural Factors and Individual Differences in Sarcasm Interpretation and Use - Zhu, Ning (2024)
There has been some debate regarding whether sarcasm mutes the negativity of criticism (the Tinge Hypothesis) or enhances condemnation. There is also some evidence that individual differences factors and speakers’ characteristics may influence sarcasm interpretation and use. However, the findings are mixed so far. Regarding the time course of sarcasm processing, there are also inconsistent findings in terms of whether sarcasm takes more time to process than literal criticism. However, previous research on sarcasm interpretation and sarcasm processing paid insufficient attention to cultural effects. This PhD thesis investigated the effects of contextual factors, such as the relative social status between the speaker and the recipient (Chapter 5), the high or low common ground shared between the speaker and the recipient (Chapter 6) in sarcasm interpretation, and individual differences, such as theory of mind ability and sarcasm use tendency, on sarcasm interpretation (Chapter 4) and sarcasm processing (Chapter 7) from a cross-cultural perspective. Results showed that: (1) sarcasm interpretation varied across cultures; while UK participants rated sarcasm as being less aggressive and more amusing than literal criticism, Chinese participants rated sarcasm as being more aggressive and more amusing. (2) Socio-cultural factors, such as the relative social status and the high or low common ground between the speaker and the recipient, influenced sarcasm interpretation and the effects of characters’ relative social status varied across cultures. (3) There were individual differences in sarcasm interpretation and the effects were modulated by culture. (4) The time course of processing sarcasm showed differences across cultures. (5) The effects of theory of mind ability on sarcasm processing might be mediated by participants’ understanding of sarcastic intent. The findings of this thesis suggest the need for a dynamic model in which socio-cultural factors and individual differences work together in influencing sarcasm interpretation and processing.